IDENTIFICATION OF FACTORS IN WORK-RELATED STRESS AMONG NURSING PROFESSIONALS - Jesús Cremades Puerto; Loreto Maciá Soler; Mª José López Montesinos; Isabel Orts Cortés (Universidade Federal do Paraná, 2011)
Interest in the study of stress and the psycho-social factors related with work has grown over recent decades. Stress may be studied in specific units, but situations of stress are frequently to be found in medical units. The objective of this study was to identify and classify work-related stress factors which affect nursing professionals in hospital units. The study was qualitative with a descripto-analytical approach, following the Delphi methodology, and was carried out in Spain at the University of Alicante General Hospital and Elda General Hospital. Thirty nursing professionals from these units participated. Different stress factors acting on the health professionals were identified in the four stages of the process, in progressively raising levels of consensus. It is concluded that the factors referred to most frequently and with the greatest consensus may be used as a tool in the clinical management of hospital units, to improve the work life of the staff and to seek excellence in management.